Teachers’ Readiness to Adopt AI for Teaching Materials Development: The Impact of AI Literacy Training at a Senior High School in Depok - Kiki Fauziah; Hanif Inamullah; Aviazka Firdhaussi; Wiwit Ratnasari; Sadewa Ersa Pamungkas; Annisa Rizky (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Background: This article analyses teachers’ readiness to adopt artificial intelligence when developing teaching materials. It explicitly measures teachers’ competency after participating in AI literacy training. Objective: This study aimed to determine whether the training can improve high school teachers’ understanding and competence in utilising generative artificial intelligence as a tool for developing teaching materials. Method: This quantitative study employed a one-group pretest–posttest design and a pre-experimental method. Fifty teachers at SMAN 1 Depok were chosen as responders using a total sampling technique. A questionnaire was used to gather information in order to assess the effectiveness of the AI literacy training program. In order to supplement the quantitative data, observations and interviews were also carried out. Results: The study's findings show that instructors at SMAN 1 Depok are highly prepared to incorporate AI into the creation of instructional materials. The AI literacy training has effectively improved the teachers’ perceptions, knowledge, and skills while applying AI in educational contexts. Conclusion: Seven variables measured in this study, which include aspects of understanding, skills, views, ethics, threat perception, innovation, and job satisfaction, experienced a statistically significant increase (p < 0.05), with a large effect size (Cohen’s d > 0.8) in almost all aspects, indicating a substantial practical impact of the training.